Effet de la couche fenetre sur les performances d’une cellule solaire à base de GaAs - Benaicha, M.; Ounissi, A. (Science des matériaux (Laboratoire LARHYSS); Vol. 7 No 02 (2016): Science des matériaux (Laboratoire LARHYSS) MAi, 2016)
Abstract- During the last years, III-V solar cells were widely used, more particularly in spatial applications, because of their high conversion efficiency and their weak degradation in front of space irradiations. This paper reports on a simulation of a GaAs solar cell using a PC1D. The properties of the top layer in a solar cell (thickness, doping,...) in particular, plays a crucial role in its performances, in order to optimise them we analysed their influence on the Photovoltaic parameters of the cell. To demonstrate the importance of the deposition of a window layer Ga 1-x Al x As on the top of a GaAs solar cell we carried out a comparison of performances between a cell with a window and a conventional GaAs cell (without window). The optimized structure gives the following results: η =26.5% end FF=86.05%. We also compare these cell performances with those of an optimised GaAs single junction solar cell to show the window layer improvement.